Factors Affecting Student’s Burnout In Online Learning - Rahmi Dwi Febriani; Triyono Triyono; Rezki Hariko; Verlanda Yuca; Elrisfa Magistarina (Universitas Negeri Padang, 2021)
The Pandemic of Corona Virus Disease (Covid-19) has a significant impact on various sectors of life, including the education sector.The learning process, which was initially carried out in person or face-to-face, is now carried out online.This virtual learning implementation has a negative impact on students' psychology, one of which is the burnout study.Several research results show that many students have difficulty understanding the material provided online, the task demands are high, and cannot interact directly with friends and lecturers.Furthermore, this increases the burnout of the study in students and causes the lecture process to be not optimal.Burnout study is a condition in which an individual feels physically and emotionally exhausted, causing boredom in learning, indifference to academic assignments, lack of motivation, laziness, and decreased learning achievement.Current research uses literature review by looking for theoretical references that are relevant to the problems found.